(3LhGH GdechOi Edi HYV CUMGHg Yf daX GdRQGaIs - (3CHhRjO YHO GdQMef Hf Ydj GdechOj GdaGSj,J (B807 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdGFb hCMSf UhQge s
(3BNQgG (B:s
(3hLH Ydi Cf CQaY gPG GdJCdja Edi GdMGLH bGeYkG HSjag cHjQ GdZOGg GdeYJOjf fGaYkG HSjHg GfJgi gPG GdJbjjO ai GdRQGaI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3Hg GfXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs